Difficulties facing art education supervisors From their point of view (Journal of the College of Basic Education, 2022)
The current research aims to identify the difficulties facing art education supervisors from their point of view.The research sample was limited to (13) supervisors, and to achieve the objectives of the research, the researcher built her research tool represented by (a questionnaire of difficulties), and it consisted of (25) items, with three alternatives (a major difficulty, a secondary difficulty, that does not constitute a difficulty). Verify its validity and stability, and the discriminatory power of its paragraphs. The researcher used the percentage equation for the purpose of extracting the percentages for each paragraph of the research tool, and the researcher reached the results